Cortical versus cancellous screws in treating medial malleolar fractures - Yammine, Kaissar (2019)
Study design Systematic review of comparative studies. Background Partially threaded (PT) cancellous screws are a common method to fix medial malleolar fractures but with reported complications due to the hardware. Fully threaded (FT) screws have been advanced as an alternative yielding similar union results with less implant-related complications. Objectives The aim of this study is to systematically collate comparative clinical and biomechanical evidence on the effectiveness and complications of the PT versus FT screw constructs in the treatment of medial malleolar fractures. Results Based on 7 studies (8 subgroups), similar weighted healing rates were found from pooling 3 clinical studies with the time to heal outcome significantly shorter following FT compared to FT screws. Complication rates in the form of screw loosening (1.97% vs. 13.4%, p = 0.008) and screw removal surgery (0% vs. 15.7%, p < 0.0001) were significantly higher after using PT screws. The five biomechanical studies demonstrated that FT screw constructs had significantly superior properties than the PT constructs and that for all outcomes. Conclusion Fully threaded screws seem to offer significantly better clinical and biomechanical outcomes when compared to the partially threaded screws in treating medial malleolar fractures. The use of headless FT screws could contribute to reduce the implant-related complications.